To the plasma wakefield excitation by a nonresonant sequence of relativistic electron bunches at plasma frequency above bunch repetition frequency - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Svistun, E.N.; Vesnovskaya, M.S. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
By using 2d3v code LCODE the investigation of plasma wakefield excitation by a nonresonant sequence of relativistic electron bunches for the case of bunch repetition frequency lower plasma frequency is carried out. Contrary to the case of nonresonant sequence with bunch repetition frequency higher plasma frequency the picture of field and bunches evolution is more complicated with no linear field growth. Nevertheless the asymmetry between the energy loss of decelerated bunches in the front half of beats and the energy gain of accelerated bunches in the rear half of beats, caused by different bunch-field coupling gives on average the growth of wakefield amplitude. С использованием 2d3v-кода LCODE проведены исследования возбуждения кильватерного поля в плазме нерезонансной цепочкой релятивистских электронных сгустков в случае, когда частота следования сгустков меньше плазменной частоты. В отличие от случая нерезонансной цепочки с частотой следования сгустков, большей плазменной частоты, картина эволюции поля и сгустков более сложная, без линейного роста поля
Тем не менее, асимметрия между потерей энергии тормозящимися сгустками в первой половине биений и приобретением энергии ускоряемыми сгустками во второй половине биений, вызванная различной связью сгустков с полем, приводит, в среднем, к росту амплитуды кильватерного поля. З використанням 2d3v-коду LCODE проведено дослідження збудження кільватерного поля у плазмі нерезонансним ланцюжком релятивістських електронних згустків у випадку, коли частота слідування згустків в плазму менше плазмової частоти. На відміну від випадку нерезонансного ланцюжка з частотою слідування згустків, більшою за плазмову частоту, картина еволюції поля та згустків більш складна, без лінійного зростання поля. Тим не менше, асиметрія між втратами енергії згустками, що гальмуються в першій половині биття та здобутком енергії згустками, що прискорюються у другій половині биття, спричинена різним зв’язком згустків з полем, призводить, у середньому, до зростання амплітуди кільватерного поля.